Pengendalian Kualitas Produk Dengan Menggunakan Metode SQC dan HRA Guna Meningkatkan Hasil Produksi Tahu di IKM H. Musauwimin - Koyor Rujianto; Hana Catur Wahyuni (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2018)
Small and Medium Industries (IKM) H.Musauwimin is a manufacturing industry in the field of tofu production. In the production process there are still frequent product defects, including coarse tofu, tofu surface torn, soft texture, and faded color. For this reason, we need a way to minimize the possibility of product defects. The objectives of this study are (1) Identifying disability factors using the Statistical Quality Control (SQC) method, (2) Improving employee performance performance using the Human Reliability Assessment (HRA) method, (3) Minimizing product defects in the production process so as to increase productivity. The results of this study are (1) of the four types of rejects for the biggest 3 months in tearing surface type with a percentage of 46% of all rejects (2) By testing the adequacy of the data using the SQC method in the production process for 3 months then sample we tested a total of 284. From the results of the data adequacy test data obtained a value of 7,289, so the number of samples is larger than the sample that should be. (3) From the results of measuring employee performance using the HRA method. The biggest HEP value is the type of Possible Error. The operator only estimates and there is no standard in mixing vinegar acid with the filtrate. With an HEP value of 0.48. So this factor is the most dominant cause of disability and must be corrected immediately.